Agricultural growth, hunger and poverty in Pakistan: A historical perspective on the agrifood systems of the indus plains (Webinar session 7) - Gazdar, Haris (International Maize and Wheat Improvement Center, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA), CGIAR Initiative is hosting a series of webinars to highlight research from South Asia on food security, sustainable healthy diets, farmer livelihoods and resilience, and land, air, and groundwater conservation. This webinar is part of TAFSSA Work Package 5: Building resilience and mitigating environmental impact.